Expected impacts of the Cannabis infringement notice scheme in Western Australia on regular users and their involvement in the cannabis market. - Chanteloup, Francoise; Lenton, Simon; Fetherston, James; Barratt, Monica (Taylor and Francis Ltd, 2005)
The effect on the cannabis market is one area of interest in the evaluation of the new 'prohibition with civil penalties' scheme for minor cannabis offences in WA. One goal of the scheme is to reduce the proportion of cannabis consumed that is supplied by large-scale suppliers that may also supply other drugs. As part of the pre-change phase of the evaluation, 100 regular (at least weekly) cannabis users were given a qualitative and quantitative interview covering knowledge and attitudes towards cannabis law, personal cannabis use, market factors, experience with the justice system and impact of legislative change. Some 85% of those who commented identified the changes as having little impact on their cannabis use. Some 89% of the 70 who intended to cultivate cannabis once the CIN scheme was introduced suggested they would grow cannabis within the two non-hydroponic plant-limit eligible for an infringement notice under the new law. Only 15% believed an increase in self-supply would undermine the large scale suppliers of cannabis in the market and allow some cannabis users to distance themselves from its unsavoury aspects. Only 11% said they would enter, or re-enter, the cannabis market as sellers as a result of the scheme introduction. Most respondents who commented believed that the impact of the legislative changes on the cannabis market would be negligible. The extent to which this happens will be addressed in the post-change phase of this research. Part of the challenge in assessing the impact of the CIN scheme on the cannabis market is that it is distinctly heterogeneous.